PENGGUNAAN SENYAWA OSMOLIT DAN ALKALIN PADA PENYADAPAN TANAMAN KARET (Hevea brasiliensis) - Mochlisin Andriyanto; Miftahul Huda Fendiyanto (Jurnal Agro Estate, 2019)
Stimulants are one of the common ways to increase yield in rubber plants. Recent, the stimulant that is widely used in rubber tapping is ethephon. Ethephon material can prolong the flow of latex so that yield increases. The combination of osmolyte and alkaline compounds is expected to be an alternative stimulant. Therefore, this study aimed to examine the use of osmolytes and alkaline in rubber plants. This research was conducted at the Experimental Design of the Sungei Putih Estate Research, Deli Serdang, North Sumatra in May-September 2016 with PB 260 clones planting year 2010 with a tapping system S/2 D3 Ga1.0 6 / y (m) in panel B0-2. The experimental design used was a Randomized Complete Block Design (RCBD) with 28 combinations of treatments. The observation parameters in this study were yield (g/p/s), girth (cm) before treatment application and yield (g/p/s) and yield (kg/ha/year) after treatment application. The observations showed that the addition of stimulants with osmolyte and alkaline compounds had a significant effect yield on rubber (g/p/s) in the first tapping slices. The 5% osmolyte and 10% alkaline compounds have yield rubber which is comparable to the application of stimulants made from ethephon in the first tapping slices. Application of 5% osmolyte and 10% alkaline compounds can be used as an alternative stimulant in rubber plants.